INTEGRASI READY DATA DAN PENGINDERAAN JAUH BERBASIS SIG UNTUK ANALISIS CEPAT PENILAIAN RISIKO BANJIR DI KECAMATAN SEMANU, GUNUNGKIDUL - Kanita Shinta Wati; Sudaryatno Sudaryatno (Indonesian National Institute of Aeronautics and Space (LAPAN), 2020)
The high number of flood events in Indonesia is influenced by weather influences such as the tropical cyclone Cempaka on 27-29 November 2017. The incident caused disasters in 28 regencies / cities in Java. Semanu District is one of the areas in Gunungkidul Regency which was affected by tropical cyclones and submerged several residents' houses to a height of 2.7 meters. Therefore, information is needed related to the risk of flooding in Semanu District. This study has three objectives, namely to obtain and collect data related to flood disasters in Semanu District, compile detailed scale scale disaster risk mapping databases in Semanu District, and map flood disaster risk in Semanu District.The SPOT 7 image, DEM Alos Palsar, and secondary data are used for the components making up the flood threat component. The amount of data used in research requires the compilation of an appropriate database to make it easier to access data that has been collected and will be processed using spatial analysis based on GIS. Disaster risk mapping is carried out taking into account the threat, vulnerability and capacity factors that produce three classes of flood risk, namely low, medium and high risk. Making a Map of Land Use as basic information for the process of flood hazard analysis has an accuracy of 94.29%.The results of this study in general the Semanu District has three flood risk classes. The